2007
DOI: 10.1128/jcm.02473-06
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Zygomycosis on Microbiology Workload: a Survey Study in Spain

Abstract: This multicenter, population-based study evaluated the laboratory workload produced by zygomycetes and the number of cases of zygomycosis in Spain during 2005. Less than 8% of the patients who harbored zygomycete isolates had zygomycosis. The incidence of zygomycosis (6 cases) was 0.43 cases/1,000,000 inhabitants and 0.62 cases/100,000 hospital admissions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
49
1
11

Year Published

2008
2008
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(62 citation statements)
references
References 27 publications
1
49
1
11
Order By: Relevance
“…A previous report by our group showed that, in 2005, Spanish microbiology laboratories isolated zygomycetes in only 6 per 100,000 samples [35]. We were unable to demonstrate any substantial increase in the isolation of zygomycetes in our institution in the last 10 years.…”
Section: Discussioncontrasting
confidence: 75%
“…A previous report by our group showed that, in 2005, Spanish microbiology laboratories isolated zygomycetes in only 6 per 100,000 samples [35]. We were unable to demonstrate any substantial increase in the isolation of zygomycetes in our institution in the last 10 years.…”
Section: Discussioncontrasting
confidence: 75%
“…For mucormycosis, we used a rate of 0.43 cases per 1 million inhabitants, as previously documented [35].…”
Section: Methodsmentioning
confidence: 99%
“…Other cases of cryptococcal meningitis occur, but we have no reliable means to estimate this. For mucormycosis, a Spanish study found an incidence rate of 0.04 cases per 100 000 inhabitants that suggests 20 cases every year [35]. However, in France, a neighbouring country, the incidence recently found was 0.12 cases per 100 000 inhabitants.…”
Section: Other Fungal Infectionsmentioning
confidence: 96%
“…En un estudio que reunió datos de 50 hospitales de España, el aislamiento de Zygomycetes fue muy bajo, demostrando que menos del 8% de los pacientes con cultivo positivo estaban realmente infectados, mientras que la gran mayoría presentaban colonización o contaminación de laboratorio (33). Aún así, consideramos que, si bien la trascendencia del cultivo puede ser baja, el aislamiento de estos hongos tiene importancia si se considera el tipo de lesión y procedencia de la muestra clínica.…”
Section: Discusionunclassified
“…En estos últimos años se ha descrito un incremento importante en la incidencia de esta enfermedad en instituciones aisladas o unidades específicas alcanzando un 8% en pacientes con leucemia. Este aumento del número de casos se produce generalmente en pacientes y unidades donde se administra con exceso profilaxis antibacteriana de amplio espectro, sin la sospecha de una micosis (33). …”
Section: Discusionunclassified